Analysis of Water Biological Factors, Pests and Diseases of Seaweed in Sialong Hamlet, Batu Boy Village, Buru District as an Impact of Crop Failure - Zakariah, Muhammad Ikbal; Irsan, Irsan; Laitupa, Jufri Pachri; Mangesa, Rosita; Koto, Saifuddin; Fesanrey, Wilda; Umasugi, Samsia; Nurlatu, Umiati Hasanah (Agrikan Jurnal Agribisnis Perikanan, 2024)
The study was conducted from August to September 2024 at the seaweed cultivation location in Kaiely Bay, with sampling at three observation stations. The method used was a survey with a laboratory approach. The parameters analyzed included phytoplankton abundance, chlorophyll-a content, and identification of pests and diseases in seaweed. The data obtained were analyzed descriptively. The results of the study showed that the abundance of phytoplankton at the three research stations was very high (eutrophic) with the highest value at Station 2 (8,133,333.33 cells/L) and the lowest at Station 3 (6,043,333.33 cells/L). Chlorophyll-a at all stations was in the eutrophic category with the highest concentration at Station 2 (0.00137 mg/L). The types of pests found at all stations were chicken fish, rabbitfish, and turtles. There were two types of bacteria found, namely station 1 pathogenic bacteria Pseudomonas aeruginosa, station 2 and station 3 types of Vibrio. Thallus morphology at station 1 was: gouging and stripping, station 2 was stripping, tip-nipping and ice-ice and station 3 was gouging, stripping, tip-nipping, and ice-ice.